A fifty-year odyssey: prospects for a cytomegalovirus vaccine in transplant and congenital infection - Don Jeffrey Diamond; Corinna La Rosa; Flavia Chiuppesi; Heidi Contreras; Sanjeet Dadwal; Felix Wussow; Supriya Bautista; Ryotaro Nakamura; John A. Zaia (Expert Review of Vaccines, 2018)
Introduction: It has been almost fifty years since the Towne strain was used by Plotkin and collaborators as the first vaccine candidate for cytomegalovirus (CMV). While that approach showed partial efficacy, there have been a multitude of challenges to improve on the promise of a CMV vaccine. Efforts have been dichotomized into a therapeutic vaccine for patients with CMV-infected allografts, either stem cells or solid organ, and a prophylactic vaccine for congenital infection. Areas covered: This review will evaluate research prospects for a therapeutic vaccine for transplant recipients that recognizes CMV utilizing primarily T cell responses. Similarly, we will provide an extensive discussion on attempts to develop a vaccine to prevent the manifestations of congenital infection, based on eliciting a humoral anti-CMV protective response. The review will also describe newer developments that have upended the efforts toward such a vaccine through the discovery of a second pathway of CMV infection that utilizes an alternative receptor for entry using a series of antigens that have been determined to be important for prevention of infection. Expert commentary: There is a concerted effort to unify separate therapeutic and prophylactic vaccine strategies into a single delivery agent that would be effective for both transplant-related and congenital infection.